2017
DOI: 10.1111/nph.14864
|View full text |Cite
|
Sign up to set email alerts
|

The cotton (Gossypium hirsutum) NAC transcription factor (FSN1) as a positive regulator participates in controlling secondary cell wall biosynthesis and modification of fibers

Abstract: Cotton (Gossypium hirsutum) fibers are the highly elongated and thickened single-cell trichomes on the seed epidermis. However, little is known about the molecular base of fiber cell wall thickening in detail. In this study, a cotton NAC transcription factor (GhFSN1) that is specifically expressed in secondary cell wall (SCW) thickening fibers was functionally characterized. The GhFSN1 transgenic cotton plants were generated to study how FSN1 regulates fiber SCW formation. Up-regulation of GhFSN1 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 46 publications
4
89
0
Order By: Relevance
“…This phenomenon was also observed in other plants, such as in tartary buckwheat and cassava [44,52]. Moreover, several reports have indicated that overexpression of tissue-specifically expressed NAC genes can promote the development of particular tissues, as NAC4 from tomato promoted fruit ripening and carotenoid accumulation [23], cotton NAC transcription factor 1 was involved in secondary cell wall biosynthesis and modification of fibers [19]. Seven highly expressed PmNAC genes (FPKM > 20 in all the tested tissues) originated from subgroup Pm_NAC, suggesting the important roles of the broomcorn millet-specific subgroup Pm_NAC in plant growth and development.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This phenomenon was also observed in other plants, such as in tartary buckwheat and cassava [44,52]. Moreover, several reports have indicated that overexpression of tissue-specifically expressed NAC genes can promote the development of particular tissues, as NAC4 from tomato promoted fruit ripening and carotenoid accumulation [23], cotton NAC transcription factor 1 was involved in secondary cell wall biosynthesis and modification of fibers [19]. Seven highly expressed PmNAC genes (FPKM > 20 in all the tested tissues) originated from subgroup Pm_NAC, suggesting the important roles of the broomcorn millet-specific subgroup Pm_NAC in plant growth and development.…”
Section: Discussionmentioning
confidence: 62%
“…To further investigate the structural features of broomcorn millet NACs, the conserved motif distributions were analysed. A total of 20 conserved motifs (referred to as motifs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were identified by MEME, with more motifs located within the N-terminal region than within the C-terminal region (Fig. 2c).…”
Section: Protein Properties and Sequence Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Full length Nucleus Enhances tolerance to drought and salinity [53] 18 GhFSN1 (Gossypium hirsutum) Full length and C-terminal Nucleus Controls secondary cell wall biosynthesis and modification of fibers [127] 19…”
Section: Full Length and C-terminal Nucleusmentioning
confidence: 99%
“…They are also involved in the signaling pathway induced during biotic and abiotic stresses [18,21,22], and in the regulation of leaf senescence [23]. As for secondary growth, NAC TFs have been described in the regulation of xylogenesis, fiber development, and secondary cell wall formation [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%